Japanese governance beyond Japan Inc. - Amyx, Jennifer Ann; Drysdale, Peter (Politics in Asia series, 2003)
Japan Inc was once used to describe the powerful political and economic system that delivers Japan's transformation to an industrial power. This book is about the breakdown and failure of policy coherence in Japan in the 1990s and how the political economy of Japan has changed in response. The essays in the volume seek to identify where change has occurred, as well as where things have not changed and why. The issue of policymaking transparency is accorded particular attention. The book covers a wide range of Japanese institutions and policy areas, including the political party system, electoral and legal reforms, deliberation councils and the financial and agricultural sectors. The findings suggest that resistance to change through the political system is at the root of Japan's inability to deal with its national policy problems. Nonetheless, there has been considerable reform and change towards more open economic and political competition. And, these changes profoundly affect the way in which foreign governments must now relate to domestic political processes in their dealings with Japan. This interdisciplinary book draws together contributions from experts in political science, economics, law and Japanese studies to give a deeper understanding of how Japan's political economy and policymaking processes are working today.